Revitalizing Da’wah Against Communication Chaos in the Modern Era: Content Analysis of Piweling Maiyah’s YouTube Content - Yusuf, Mochamad Aris (Al-I'lam: Jurnal Komunikasi dan Penyiaran Islam, 2024)
Abstract:Domestic disputes that destroy relationships simply through miscommunication have given rise to sad facts, such as cases of murder, mutilation, sex outside of marriage and so on.  So, communication must be integrated with Islamic da'wah as well as responding to the challenges of the times. This has been practiced by Cak Nun, known as Maiyah.  Maiyah Da'wah emphasizes a holistic understanding of life, where every individual is invited to become a wise, tolerant person and contribute positively to the surrounding environment. This research uses a content analysis method, the object in this research focuses on content Piweling Maiyah which is entitled Learning to Find Goals - Cak Nun. The results in this research show that life is emphasized on YouTube channels Piweling Maiyah Firstly, in improving life towards becoming a human being who is sovereign and can save himself before Allah SWT. This is revitalizing, making humans have a way of thinking positively and bringing a level of expression of communication, a mentality based on strong faith.Abstrak:Pertikaian rumah tangga yang meruntuhkan hubungan hanya dengan miskomunaksi telah menimbulkan fakta miris, seperti kasus pembunuhan, mutilasi, sex diluar nikah dan lain-lain.  Maka, komunikasi harus dilebur dengan dakwah islam sekaligus menjawab tantangan zaman. Hal ini telah dipraktekkan oleh Cak Nun yang dikenal dengan nama Maiyah.  Dakwah Maiyah menekankan pada pemahaman holistik tentang kehidupan, di mana setiap individu diajak untuk menjadi pribadi yang bijak, toleran, dan berkontribusi positif terhadap lingkungan sekitarnya. Penelitian ini menggunakan metode analisis isi, objek dalam penelitian ini menitik fokuskan pada konten Piweling Maiyah yang berjudul Belajar Mencari Golnya itu apa – Cak Nun. Hasil dalam penelitian ini, kehidupan yang ditekankan dalam kanal YouTube Piweling Maiyah tersebut, pertama dalam memperbaiki hidup menuju manusia yang bedaulat dan bisa menyelamatkan diri dihadapan Allah SWT, Hal ini merevitalisasi, menjadikan manusia memiliki cara dalam berfikir positif dan membawa tingkat ekspresi komunikasi mentalitas berlandaskan iman yang kuat.